Effective evaluation of projects on violence against women and girls. Issue 4 (19th May 2018) - Raab, Michaela; Stuppert, Wolfgang
ABSTRACT: What makes evaluations useful for interventions on violence against women and girls (VAWG)? This article reports on a qualitative comparative analysis of 39 evaluations, and shows that it takes a combination of elements to produce good evaluation effects. It identifies eight configurations of conditions which have generated effective evaluations. Key elements were the evaluation context, the evaluators' sensitivity to gender and to the participants' rights and security, and consultation with persons considered to be the ultimate "beneficiaries" of the intervention. Both qualitative and quantitative approaches could lead to effective evaluation. The article concludes with recommendations for evaluation users.